Knowledge and self-care practices of diabetic patients in an urban community - Gupta, Dipali; Agrawal, Nipun; Agrawal, Suresh C.; Singh, Atul K.; Gupta, Shyam B. (International Journal Of Community Medicine And Public Health, 2021)
Background: The term "diabetes mellitus" describes a metabolic disorder of multiple aetiology characterized by chronic hyperglycemia. The GOI’s NPCDCS has a focus on awareness generation for behaviour and life-style changes, screening and early diagnosis of persons with high level of risk factors and their referral to appropriate treatment facilities. Earlier studies have reported that knowledge of patients about diabetes care leads to better glycemic control. Methods: A cross-sectional study conducted over a period of 3 months among diabetic patients coming to private OPD in Bareilly city. Patients with any other serious morbidity were excluded from the study. Results: Mean age was 61.8±13.4 years. Mostly subjects did not know the type of diabetes they had (42, 75.0%) amongst those who knew, majority had type-2 diabetes (9, 16.1%). Majority had no known history of diabetes in the family (31, 55.4%). Most of the study subjects had diabetes diagnosed for five years or less (26, 46.4%). Most common co-morbidity was hypertension (33, 58.9%) followed by obesity (29, 51.8%). Majority of subjects (23, 41.1%) followed some dietary advice and a little less than half performed exercise daily. Approximately two-third of the subjects (38, 67.9%) did not have blood sugar testing in the previous week and most subjects (31, 55.4%) did not care for their feet. Majority (39, 69.6%) took regular medicine. Conclusions: It is evident that better education is related to good self-care. Masses need to be made aware regarding self-care emphasizing on foot care and regular blood sugar testing.